2016
DOI: 10.1142/s0217732316502102
|View full text |Cite
|
Sign up to set email alerts
|

Modelling quantum black holes

Abstract: Novel bound states are obtained for manifolds with singular potentials. These singular potentials require proper boundary conditions across boundaries. The number of bound states match nicely with what we would expect for blackholes. Also they serve to model membrane mechanism for the blackhole horizons in simpler contexts. The singular potentials can also mimic expanding boundaries elegantly, there by obtaining appropriately tuned radiation rates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…In Fig.1 we plot two configurations in two dimensions which illustrate the results of Propositions 1 and 2. The results obtained in [37] for d = 2 and d = 3 are recovered when |w 0 |x 0 |w 1 | (for d = 3 there is minus sign and the integer part missing). To end this section, let us briefly study the behaviour of the number of negative energy eigenvalues as a function of the dimension d and the angular momentum .…”
Section: On the Number Of Bound Statesmentioning
confidence: 84%
See 4 more Smart Citations
“…In Fig.1 we plot two configurations in two dimensions which illustrate the results of Propositions 1 and 2. The results obtained in [37] for d = 2 and d = 3 are recovered when |w 0 |x 0 |w 1 | (for d = 3 there is minus sign and the integer part missing). To end this section, let us briefly study the behaviour of the number of negative energy eigenvalues as a function of the dimension d and the angular momentum .…”
Section: On the Number Of Bound Statesmentioning
confidence: 84%
“…We have introduced a rigorous and consistent definition of the potential V δ-δ = w 0 δ(x − x 0 ) + 2w 1 δ (x − x 0 ) in arbitrary dimension, characterizing a selfadjoint extension of the Hamiltonian H 0 (14) defined on R x 0 . In doing so, we have corrected the matching conditons in [37] for the two and three dimensional V δ-δ potential. We have shown that the Dirac-δ coupling requires a re-definition which also depends on the radius x 0 and the δ coupling w 1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations